Achieving greater equity in allocation of catch shares: A case study in China - Ding, Qi; Shan, Xiujuan; Jin, Xianshi; Gorfine, Harry (Frontiers in Marine Science, 2022)
The allocation of catch shares among fishing entities is a key element of a total allowable catch control system. Current allocation schemes fall short in their ability in terms of ensuring fairness and feasibility and there is much scope for improvement. In this study, a new allocation method based on applying a relative deprivation coefficient is introduced into the allocation of catch shares, and demonstrated in a case study involving the 11 coastal provinces in China. Advantages of this process of quota allocation in comparison with well-established allocation methods were investigated. Compared with the conventional single-criterion approach and simple multi-criteria-based allocation with equal weights, the new allocation scheme integrating the new weighting method with multi-criteria allocation showed superior performance in rendering the outcomes in catch shares allocation fairer and more reasonable, with a Gini coefficient below 0.2. Quota proportions for the 11 coastal provinces under the newly developed allocation scheme were between maximum and minimum ratios of those under schemes using a single-criterion, which shows strong utility in reducing the rigidity of a single-criterion allocation approach and improving the acceptability of the allocation results. This study offers a viable yet fairer alternative for facilitating sustainable fisheries via quota management and provides a reference for fisheries policy makers in equitably allocating catch shares.